Administration of host‐derived probiotics does not affect utilization of soybean meal enriched diets in juvenile turbot (Scophthalmus maximus). (10th June 2019) - Wanka, Konrad M.; Schulz, Carsten; Kloas, Werner; Wuertz, Sven
Abstract: In today's aquaculture, the cost‐intensive and scarce fishmeal is increasingly replaced by plant‐based feedstuff such as soybean meal (SBM). However, SBM contains saponins which can have adverse effects on fish's digestive tract potentially culminating in severe enteritis. In a 60 day feeding trial we studied the use of autochthonous bacteria as probiotics upon SBM supplementation on juvenile turbot. Growth performance, feed conversion, body composition and health status were assessed for five different treatment groups, comprising a fishmeal control (FM ctrl), a SBM control without probiotics (SBM ctrl) and three multi‐species probiotic treatments. For the production of the probiotic treatments a basal diet with a composition identical to the SBM ctrl including 40% SBM of total dry matter likewise was prepared. The basal diet was stepwise top coated with three different probiotic supplementations: (a) three distinct isolates with saponin‐metabolizing ability (SBM + degrad); (b) three distinct isolates inhibitory towards the pathogen, Tenacibaculum maritimum (SBM + anta); and (c) a commercial probiotic application (SBM + com). Individual weight gain was highest in FM ctrl but only SBM + degrad diet showed a significantly lower value ( p < 0.05). The feed conversion ratio was lowest in FM ctrl and significantly higher in SBM + degrad ( p < 0.01). The protein retention efficiency did only differ significantly between FM ctrl and SBM + degrad ( p < 0.05), whereas lipid retention efficiency remained unaffected. Whole body composition and gross energy content were similar in all treatments lacking significant differences. The condition factor was significantly elevated in SBM + degrad compared to FM ctrl ( p < 0.05). Hematocrit was highest in FM ctrl and significantly lower in the other treatments ( p < 0.01) with SBM + com accounting for the lowest value ( p < 0.001). The hepatosomatic index was slightly increased in FM ctrl but no significant difference was detected. Regarding the spleen somatic index SBM + anta treatment revealed the highest and SBM ctrl a significantly lower value ( p < 0.05). In conclusion, the growth performance of fish did not benefit from the different probiotic treatments, while body composition and gross energy content remained at an appropriate level. Moreover, the overall health status was on a sufficient level in all treatments which confirms the high dietary tolerability of our putative probiotic isolates by the fish.